Follow the light: projector-based augmented reality intracorporeal system for laparoscopic surgery - Edgcumbe, Philip (J Med Imaging (Bellingham), 2018)
A projector-based augmented reality intracorporeal system (PARIS) is presented that includes a miniature tracked projector, tracked marker, and laparoscopic ultrasound (LUS) transducer. PARIS was developed to improve the efficacy and safety of laparoscopic partial nephrectomy (LPN). In particular, it has been demonstrated to effectively assist in the identification of tumor boundaries during surgery and to improve the surgeon’s understanding of the underlying anatomy. PARIS achieves this by displaying the orthographic projection of the cancerous tumor on the kidney’s surface. The performance of PARIS was evaluated in a user study with two surgeons who performed 32 simulated robot-assisted partial nephrectomies. They performed 16 simulated partial nephrectomies with PARIS for guidance and 16 simulated partial nephrectomies with only an LUS transducer for guidance. With PARIS, there was a significant reduction [30% ([Formula: see text])] in the amount of healthy tissue excised and a trend toward a more accurate dissection around the tumor and more negative margins. The combined point tracking and reprojection root-mean-square error of PARIS was 0.8 mm. PARIS’ proven ability to improve key metrics of LPN surgery and qualitative feedback from surgeons about PARIS supports the hypothesis that it is an effective surgical navigation tool.